2001
DOI: 10.1111/j.1365-246x.2001.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Stratified multifractal magnetization and surface geomagnetic fields-I. Spectral analysis and modelling

Abstract: SUMMAR YScaling models of geofields attempt to capture the strong and wide-range variability ubiquitous in geosystems. Unfortunately, they are generally both isotropic (self-similar) and monofractal (non-intermittent, quasi-Gaussian). In this first paper of a two-paper series, we lift the first of these restrictions, arguing that anisotropic scaling is essential for taking into account the stratification of the Earth and its consequences. In particular, at horizontal scales below several thousand kilometres we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The crust is composed of multiple layers that may be characterized by different magnetic properties (different fractal parameters) yielding a radial power spectrum possibly more complicated than predicted by equation (4). The fractal parameter might vary with the wavelength [e.g., Gettings , 2005; Pecknold et al , 2001] or depend on the direction (i.e., vertical versus horizontal) [e.g., Lovejoy et al , 2001]. The model parameters z t , Δ z , and β might vary within the computational window.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The crust is composed of multiple layers that may be characterized by different magnetic properties (different fractal parameters) yielding a radial power spectrum possibly more complicated than predicted by equation (4). The fractal parameter might vary with the wavelength [e.g., Gettings , 2005; Pecknold et al , 2001] or depend on the direction (i.e., vertical versus horizontal) [e.g., Lovejoy et al , 2001]. The model parameters z t , Δ z , and β might vary within the computational window.…”
Section: Discussionmentioning
confidence: 99%
“…Early methods assumed that crustal magnetization is a completely random function of position characterized by a flat power density spectrum [e.g., Connard et al , 1983; Blakely , 1988; Tanaka et al , 1999; Ross et al , 2006]. However, other studies have suggested that crustal magnetization more closely follows fractal behavior [e.g., Pilkington et al , 1994; Maus and Dimri , 1995, 1996; Lovejoy et al , 2001; Pecknold et al , 2001; Gettings , 2005]. The method used in the present study is derived from a method initially developed by Maus et al [1997] that incorporates a model of fractal random magnetization, thus providing a more realistic representation for crustal magnetization.…”
Section: Introductionmentioning
confidence: 99%
“…The multifractal distribution of sources is another unexplored area, however some work has been carried out for the multifractal distribution of susceptibility (Fedi 2003;Fedi et al 2005b;Gettings 2005Gettings , 2012 although its use in the estimation of depth of anomalous sources has not yet been explored. Lovejoy et al (2001) suggested that anisotropic scaling is suitable for modelling the stratified earth and its magnetic field at higher and intermediate wavenumber ranges. Pecknold et al (2001) found that assumption of quasi-Gaussian statistics results in isotropic scaling behaviour of the magnetic field, otherwise it is anisotropic multifractal.…”
Section: O N C L U S I O Nmentioning
confidence: 99%
“…At regional and crustal scales, Maus and Dimri (1994) and Pilkington and Todoeschuck (1995) have shown that distributions of magnetic susceptibilities can be modeled with fractals. Further work by Lovejoy et al (2001) and Pecknold et al (2001) demonstrated that at these scales the distributions are multifractal. At sub-regional scales, drill hole logs of magnetic susceptibility were well modeled with fractals by Pilkington and Todoeschuck (1993) and were shown to be multifractal in general by Gettings (1995), Fedi (2003), Gettings (2005) and Bansal et al (2010).…”
Section: Introductionmentioning
confidence: 99%